Soot Precursor and PM Formation in Diffusion Flame Using Thermally Decomposed Aliphatic Diesel Fuel - Noge, Hirofumi; Yoshihara, Yuuichi; Kidoguchi, Yoshiyuki; Miwa, Kei (Nihon Kikai Gakkai rombunshuu. B hen, 2007)
Experimental work was performed to investigate formation of soot precursor and PM in diesel combustion process using a flow reactor and a laminar co-flow diffusion burner. Thermally decomposed aliphatic diesel fuel produced in the flow reactor was supplied directly to the burner as fuel. Measurements were conducted in the flow reactor, in the flame, and the exhaust for light hydrocarbons, low molecular weight aromatics, PAHs, soot precursor, and PM. Results show that many PAHs ranging from two to five-member ring are already formed as well as light hydrocarbon such as C2H2 and CH., during pyrolysis in the flow reactor. Exhaust PM is subject to be formed when abundant C2H2, Benzene, PAHs are produced during high temperature thermal decomposition of aliphatic diesel fuel, and the structure of PM has long chain-like aggregation. Measured fluorescence spectrometry indicates 464 nm peak. This peak is caused by soot precursor, which is in the SOF extracted from PM.